QODARIYAH DALAM SOROTAN HADIS - Agusman Damanik (UIN Sumatera Utara Medan, 2019)
Qodariyah is synonymous with one of the streams in the science of kalam which holds that humans determine qadar as a behavior, both good and bad. Historically on the theological dimension, Qodariyah was the flow that was first raised by Ma 'bad Aljuhaini ghulam Dimasqy. Qadariyah comes from Arabic, namely qadara which means ability and strength. The terminology / term is a school that believes that all human actions are not intervened by God. Imam Nawawi said,